PENGARUH FLUKTUASI HARGA MINYAK DUNIA TERHADAP VARIABEL MAKRO EKONOMI INDONESIA - Resi Yunita; Yeniwati Yeniwati (Jurnal Kajian Ekonomi dan Pembangunan, 2021)
This study aims to analyze the effect of fluctuations in world oil prices on Indonesian macroeconomic variables. The data used in this study is time series data from 1987 to 2019 taken from the World Bank, the Central Statistics Agency and FRED Economic Data. This study is a quantitative study using secondary data and the VAR/VECM analysis model. The results show that fluctuations in world oil prices are only significant in the long term while in the short term fluctuations in world oil prices have insignificant effects on inflation, economic growth and impacts. This shows that world oil prices have a significant influence on Indonesia's macroeconomic variables in the long run.